2000
DOI: 10.1046/j.1365-2168.2000.01420-10.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cognitive function and S100 production after carotid endarterectomy under local or general anaesthetic

Abstract: Background: Previous studies reported both improved (enhanced cerebral perfusion after carotid endarterectomy (CEA)) and diminished (intraoperative ischaemic injury) cognitive function (CF) following CEA. These studies were not adequately controlled for anxiety, general health and learning (repeated testing), and the influence of anaesthetic technique was not assessed. Methods: This study assessed CF (trained psychologist, seven computerized tests) before operation, and at 5 and 90 days after CEA performed und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…eral and local anaesthesia is usually attributed to the The preservation of normal cerebrovascular physideficiencies in the various monitoring techniques, ology during loco-regional anaesthesia may prevent there is also evidence that physiological protective cerebral injury during carotid endarterectomy. Data mechanisms may be preserved when local anaesthesia from Calvey et al, 78 who measured concentrations of is used. Using a combination of near infrared spec-S100 (a protein released by glial cells following cerebral troscopy and continuous jugular venous oximetry injury) in jugular venous blood and performed detailed McCleary et al 58 demonstrated that cerebral oxypsychometric tests on patients undergoing carotid engenation is maintained following application of the darterectomy, support this hypothesis.…”
Section: Pharmacological Cerebral Protection By General Anaestheticmentioning
confidence: 99%
“…eral and local anaesthesia is usually attributed to the The preservation of normal cerebrovascular physideficiencies in the various monitoring techniques, ology during loco-regional anaesthesia may prevent there is also evidence that physiological protective cerebral injury during carotid endarterectomy. Data mechanisms may be preserved when local anaesthesia from Calvey et al, 78 who measured concentrations of is used. Using a combination of near infrared spec-S100 (a protein released by glial cells following cerebral troscopy and continuous jugular venous oximetry injury) in jugular venous blood and performed detailed McCleary et al 58 demonstrated that cerebral oxypsychometric tests on patients undergoing carotid engenation is maintained following application of the darterectomy, support this hypothesis.…”
Section: Pharmacological Cerebral Protection By General Anaestheticmentioning
confidence: 99%